2020
DOI: 10.1021/acsami.0c07629
|View full text |Cite
|
Sign up to set email alerts
|

Covalently Grafted 2-Methacryloyloxyethyl Phosphorylcholine Networks Inhibit Fibrous Capsule Formation around Silicone Breast Implants in a Porcine Model

Abstract: The surface of human silicone breast implants is covalently grafted at a high density with a 2-methacryloyloxyethyl phosphorylcholine (MPC)-based polymer. Addition of crosslinkers is essential for enhancing the density and mechanical durability of the MPC graft. The MPC graft strongly inhibits not only adsorption but also the conformational deformation of fibrinogen, resulting in the exposure of a buried amino acid sequence, γ377−395, which is recognized by inflammatory cells. Furthermore, the numbers of adher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 67 publications
2
12
0
Order By: Relevance
“…In previous studies, the use of PMPC-coated hydrophilic surfaces dramatically reduced the adsorption of proteins and fibrinogens [ 17 , 40 ]. Moreover, clinical applications of PMPC in silicone implants showed that they exhibit high biocompatibility as they induce lower levels of fibrous capsular formation and also inhibit the expression of inflammatory markers, such as myeloperoxidase, TGF-β, and α-smooth muscle actin, in surrounding tissues by 20%–30% compared to non-grafted implants [ 17 , 47 ]. The present study also showed that the AGVs wPMPC suppress fibrosis in the conjunctiva by reducing the number of inflammatory cells and the fibrous capsular thickness.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the use of PMPC-coated hydrophilic surfaces dramatically reduced the adsorption of proteins and fibrinogens [ 17 , 40 ]. Moreover, clinical applications of PMPC in silicone implants showed that they exhibit high biocompatibility as they induce lower levels of fibrous capsular formation and also inhibit the expression of inflammatory markers, such as myeloperoxidase, TGF-β, and α-smooth muscle actin, in surrounding tissues by 20%–30% compared to non-grafted implants [ 17 , 47 ]. The present study also showed that the AGVs wPMPC suppress fibrosis in the conjunctiva by reducing the number of inflammatory cells and the fibrous capsular thickness.…”
Section: Discussionmentioning
confidence: 99%
“…PDMS is a common material of breast silicone that is initiated before covalent bonding with PMPC via photo-or heat-induced radical polymerization. [88][89][90][91] Ham et al grafted a nanolayer of PMPC on PDMS silicone by simply dipping the silicone in a mixture of MPC and ethylene glycol dimethacrylate, and irradiating the silicone with UV light. The covalently grafted PMPC silicone was implanted in a Yorkshire pig for 6 months and showed excellent anti-inflammation and anti-fibrous capsule behavior, as displayed in Fig.…”
Section: Artificial Implantsmentioning
confidence: 99%
“…4B. 90 Kang et al introduced heat-induced polymerization as an alternative to UV-induced polymerization. 91 They immersed a silicone breast in an initiator mixture solution of benzoyl peroxide and dipentaerythritol penta-/ hexa-acrylate in dichloromethane/acetone for 16 h at 70 1C.…”
Section: Artificial Implantsmentioning
confidence: 99%
“…Therefore, for subsequent use in patients diagnosed with severe pathologies associated with high graft rejection risk, 2-methacryloyloxyethyl phosphorylcholine (MPC) was incorporated into the RHCIII implants as interpenetrating networks [Islam et al, 2018]. MPC has been shown to have inflammation suppressing properties [Yumoto et al, 2015], which may be due to its anti-fouling properties that includes preventing the adhesion of inflammatory cells such as macrophages [Ham et al, 2020]. The resulting RHCIII-MPC implants were able to promote stable regeneration in high-risk corneas with ulcers and scarring over the observation period of an average of 2 years [Islam et al, 2018].…”
Section: Implant Design Considerationsmentioning
confidence: 99%